Parenting stress and coping strategies adopted among working and non-working mothers and its association with socio-demographic variables: A cross-sectional study - Ridhi Rajgariah; Smitha Malenahalli Chandrashekarappa; Dr Kirthana Venkatesh Babu; Arun Gopi; Narayana Murthy Mysore Ramaiha; Jagdish Kumar (Elsevier, 2021)
Introduction: Dual responsibility of women as home maker and mother intensifies stress with respect to childcare and rearing in working mothers leading to lower quality of parent - child relationship, influencing the mental health of parents and children during their developing years. Objective: (1) To determine and compare parenting stress among working and non-working mothers (2) To determine and compare coping strategies adopted by working and non-working mothers to combat parenting stress (3) Assess association of socio-demographic variables with parenting stress between the two groups. Methodology: It is a Cross-sectional study, conducted among working and non-working mothers attending immunization clinic. Data on socio-demographic variables, parenting stress (parenting stress scale) and coping strategies (cope inventory) adopted was obtained through a self-administered, validated questionnaire and analyzed using SPSS V.24. Results: 13% of non-working women and 26% of working women experienced high stress and apart from working status of the mother, there was no significant statistical difference seen between the parenting stress scores with respect to any other socio-demographic variables under consideration. Significant difference was seen with respect to the scores of Religious coping (p = 0.020), Behavioural disengagement (p = 0.003) and Acceptance (p = 0.05) as coping strategies between the working and non-working mothers Conclusions: Significant proportion of working mothers in comparison to non-working mothers had parenting stress, necessitating interventions in the form of promotion of mental health and provision of creche facility at work place.